History of the Spanish Federation of the Gas, Electricity and similar industries Workers and its newsletter, La Turbina - Fernández-Paradas, Mercedes; Rodríguez-Martín, Nuria (Hispania Nova, 2021)
e gas sector has received much attention by economic Spanish historians, particularly the role of employers and businessmen. However, there has been a lack of attention on workers of this sector. This paper aims to fill this historiographic gap, by examining the contents of an example of labour press, La Turbina, a socialist newsletter published between 1927 and 1933. Specifically, the paper examines the main characteristics of La Turbina alongside the information provided about the Spanish Federation of the Gas, Electricity and Similar Industries Workers and its concerns. Conclusions point, firstly how weakness this socialist Federation was despite the high number of workers employed in the energy sector in Spain at that time. Secondly, its support to the Comités Paritarios and the Jurados Mixtos, and finally, the crisis suffered by the organization as a result of ith anarchists that eventually led to the end of the newsletter.